Climate change and its influence on groundwater resources - Panwar S; Chakrapani GJ (Current Science, 2013)
Climate change is commonly discussed at national and international levels. It directly affects the water cycle and thus life on Earth. The effect of climate change on surface water has been known for quite sometime now, however research is still in its infancy on the effects of climate change on the surface water This review provides an insight into the factors responsible for climate change, its effects on groundwater quantity and quality on a global scale with emphasis on Indian groundwater resources and anticipated mitigation strategies.
Keywords: Aquifers; Climate change; Groundwater zones; Mitigation strategies; Sea-water intrusion